Ventral hippocampus neurons encode meal-related memory - Léa Décarie-Spain; Cindy Gu; Logan Tierno Lauer; Keshav S. Subramanian; Samar N. Chehimi; Alicia E. Kao; Serena X. Gao; Iris Deng; Alexander G. Bashaw; Molly E. Klug; Jessica J. Rea; Alice I. Waldow; et al. (Nature Communications)
Abstract The ability to encode and retrieve meal-related information is critical to efficiently guide energy acquisition and consumption, yet the underlying neural processes remain elusive. Here we reveal that ventral hippocampus (HPCv) neuronal activity dynamically elevates between eating bouts during meal consumption and this response is predictive of performance in a foraging-related memory test for the spatial location of a previously consumed meal. Targeted recombination-mediated ablation of HPCv meal-responsive neurons impairs meal location memory without influencing food motivation or spatial memory for escape location. These HPCv meal-responsive neurons project to the lateral hypothalamic area (LHA) and are enriched in serotonin 2a receptors (5HT2aR). Either chemogenetic silencing of HPCv-to-LHA projections or intra-HPCv 5HT2aR antagonist yielded meal location memory deficits, as well as increased caloric intake driven by shorter temporal intervals between meals. Collective results identify a population of HPCv neurons in male rats that dynamically respond during eating to encode meal-related memories.